Da assistência à prevenção: discursos, saberes e práticas psiquiátricas no Brasil - Oliveira, William Vaz de (2009)
This paper seeks to understand the movement of the construction of discourses and psychiatry practices in Brazil and specially in São Paulo, since the construction of specific places for madness treatment, until the consolidation of a psychiatry that used to go beyond the walls of the hospital expanding its intervention fields into the society. From a reading based on the ideas of Michel Foucault on the relationship between knowledge and power was the scientific discourse on mental illness in Brazil and its relation to the modernization, progress and civilization ideals. During the nineteenth century, the abandon situation in which the "mad people" were in Brazil, was very large. Throughout the country, before the creation of specific places for treating mentally ill people, they used to live the Holy Houses of Mercy, among patients of all sorts, living in true promiscuity conditions. However, as the medicine began entering the social circle the mad people were seen as deviant in the eyes of this new medicine and were transformed into mental patients. Thus, ways to isolate them from society were created, from the organization of specific places and institutions, providing a regular and orderly distribution of patients, keeping their bodies and minds under constant surveillance. Though in the twentieth century new psychiatric discourses and practices towards the development and use of scientific techniques, achieved significant area within psychiatry, turning not only to asylum practices, but also for society as a proposal for prevention and prophylaxis of mental illness. Accordingly, this research sought to examine the constituent elements of these psychiatry discourses and practices in Brazil, especially in Juquery Hospital in São Paulo, in the passage of the nineteenth to the twentieth century setting of the series which they belong, indicating thus the analysis method which they depend on, trying to recognize the phenomena regularities and the emergence probable limits. It did not attempt to understand these psychiatry events through a cause and effect game, what it did, in fact, was to establish the various series, decussate, seeking to understand the events in psychiatry field of that time from their emergence conditions.